Under-recognition of Acute Kidney Injury after Cardiac Surgery in the ICU Impedes Early Detection and Prevention - Schanz, Moritz; Schöffski, Oliver; Kimmel, Martin; Oberacker, Tina; Goebel, Nora; Franke, Ulrich F. W.; Alscher, Mark Dominik; Ketteler, Markus; Schricker, Severin (Kidney & Blood Pressure Research, 2021)
Background: Acute kidney injury (AKI) is associated with high morbidity and mortality; therefore, prevention is important. The aim of this study was to systematically assess AKI incidence after cardiac surgery as documented in clinical routine compared to the real incidence because AKI may be under-recognized in clinical practice. Further, its postoperative management was compared to Kidney Disease: Improving Global Outcomes (KDIGO) recommendations because recognition and adequate treatment represent the fundamental cornerstone in the prevention and management of AKI. Methods: This retrospective single-center study included n = 100 patients who underwent cardiac surgery with cardiopulmonary bypass. The coded incidence of postoperative AKI during intensive care unit stay after surgery was compared to the real AKI incidence. Furthermore, conformity of postoperative parameters with KDIGO recommendations for AKI prevention and management was reviewed. Results: We found a considerable discrepancy between coded and real incidence, and conformity with KDIGO recommendations was found to be relatively low. The coded incidence was significantly lower (n = 12 vs. n = 52, p < 0.05), representing a coding rate of 23.1%. Regarding postoperative management, 90% of all patients had at least 1 episode with mean arterial pressure <65 mm Hg within the first 72 h. Furthermore, regarding other preventive parameters (avoiding hyperglycemia, stopping angiotensin-converting enzyme inhibitors/angiotensin receptor blockers, avoiding contrast media, and nephrotoxic drugs), only 10 patients (20.8%) in the non-AKI group and in 5 (9.6%) subjects in the AKI group had none of all the above potential AKI-promoting factors. Conclusions: AKI recognition in everyday clinical routine seems to be low, especially in lower AKI stages, and the current postoperative management still offers potential for optimization. Possibly, higher AKI awareness and stricter postoperative management could already achieve significant effects in prevention and treatment of AKI.
CRIS-Team WoS Importer:2021-12-03